Rekonstruksi Pasar Bunga di Juanda Kabupaten Sidoarjo Menjadi Garden Cafe - Muhammad Aulia Kurniawan (CV. Dalle’ Deceng Abeeayla, 2024)
This study aims to examine the reconstruction of Juanda Flower Market in Sidoarjo Regency into a garden concept cafe as an effort to revitalize the market and improve the local economy. The research used qualitative methods through in-depth interviews with the target group to analyze visitor preferences related to design, menu and expected experience. The process of reconstructing the flower market into a garden café is a form of sustainable development to have a positive impact on society and the environment. In the stages of garden café reconstruction, several stages are needed, namely concept or theme development, strategic location, environmental conditions, maintenance and promotion strategies. The results showed that the concept of a garden café featuring greenery and a natural atmosphere has the potential to attract more visitors and increase the income of local communities. The café not only functions as a place to relax, but also as an educational center through organizing events about plants that strengthen human relationships with the environment. This reconstruction has proven to empower local farmers, strengthen agrarian communities, and increase environmental awareness among the public. It can be concluded that the development of a garden concept cafe is a strategic solution to revitalize the Juanda Flower Market that can provide economic benefits while supporting environmental sustainability.